The Role of Family Intervention Program in Promoting Good Mental Health Among High Risk Adolescents - Janon, Nazariah Shar'ie; Mohd Mahudin, Nor Diana; Alwi, Azlin (2020)
The topic is to present the role of family intervention programme in promoting good mental health among high risk adolescents. The programme was developed by a group of researchers from the Department of Psychology, IIUM and named as Remaja Bijak, Keluarga Prihatin. The programme was conducted to increased knowledge and skills in both parents and adolescents in promoting mental health by reducing the risk to drug used and abused. The results of the assessment before and after the intervention programme demonstrated that parents and adolescents gained significant understanding on knowledge and skills in preventing drug abused and protecting mental health through the programme modules.